PERAN ORANG TUA DALAM MENANAMKAN PENDIDIKAN ISLAM PADA ANAK DI KELUARGA BEDA AGAMA (Studi Kasus di Desa Kayu Kebek, Kecamatan Tutur, Kabupaten Pasuruan) - Sarifatul Mutnaeni; Ahmad Marzuki; Askhabul Kirom (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2022)
The role of parents is one of the important factors in instilling Islamic education in children. Giving Islamic education to children in families who share the same religion is a common thing to do. However, it is different if the family that becomes the child's first education is a family of different religions. The method in this study uses a case study approach. The type of research used is qualitative research. The data of this research were obtained by using observation, interview, and documentation techniques. Furthermore, the data is analyzed and checked for validity using triangulation of sources, techniques and time. This research was conducted in Kayukebek Village, Tutur District, where in the village there are families of different religions. The results of this study include: The role of parents in instilling Islamic education in children in interfaith families, namely as educators, being an example or role model for children, providing motivation, being a supervisor, and providing facilities.